INFLUENCE OF WATER MASS TRANSFER ON ACCURACY OF GRAIN HUMIDITY MEASUREMENT INTRODUCTION - Krushevskyy, Yuriy; Boroday, Yaroslav (Scientific Works of Vinnytsia National Technical University, 2011)
The paper contains the results of experimental research of electro physical parameters of grain, on the basis of which the reasons leading to reduction of measurement accuracy of humidity performed by dielectric moisture meters are revealed. The authors suggest ways to improve the accuracy of measurements of complex permittivity of grain crops.